Understanding film theory - Etherington-Wright, Christine (b)
"Provides an approachable and extensive introduction to film theory, written by two highly experienced senior lecturers. Bringing a fresh, contemporary and accessible approach to what is often perceived to be a challenging and old-fashioned area of film studies that requires time and effort to grasp, the text illustrates why theory is important and demonstrates how it can be applied in a meaningful way."--